2018
DOI: 10.1111/cea.13227
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of the GAG‐binding CXCL9(74‐103) peptide in dinitrofluorobenzene‐induced contact hypersensitivity in mice

Abstract: The CXCL9(74-103) peptide inhibited dinitrofluorobenzene-induced infiltration of neutrophils and neutrophil-dependent inflammation in ears. Therefore, CXCL9(74-103) may be a lead molecule for the development of therapeutic peptides or peptide derivatives that compete with functional chemokines for GAG binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…The cross talk in chemokines and G protein-coupled receptors could lead to the migration of leukocytes during normal immune function. In tissue injury or infection, this interaction is a key component of the inflammatory response [12, 13]. Current studies showed that several chemokines, such as MCP-1, fractalkine, and SDF-1, have been linked to chronic and neuropathic pain and as the key inflammatory mediators in both human conditions and animal models [1416].…”
Section: Discussionmentioning
confidence: 99%
“…The cross talk in chemokines and G protein-coupled receptors could lead to the migration of leukocytes during normal immune function. In tissue injury or infection, this interaction is a key component of the inflammatory response [12, 13]. Current studies showed that several chemokines, such as MCP-1, fractalkine, and SDF-1, have been linked to chronic and neuropathic pain and as the key inflammatory mediators in both human conditions and animal models [1416].…”
Section: Discussionmentioning
confidence: 99%
“…In a murine model of antigen-induced arthritis the peptide reduced the recruitment of leukocytes, especially neutrophils, to the synovial cavity and prevented articular and cartilage damage. Moreover, CXCL9(74-103) reduced neutrophil infiltration and neutrophil-dependent inflammation in the ears of the mice in a murine contact hypersensitivity model (265).…”
Section: Chemokine-derived Gag-binding Peptidesmentioning
confidence: 96%
“…65 In a follow-up study, Vanheule and colleagues examined whether the chemokine-GAG antagonist CXCL974-103 inhibited inflammation and neutrophildependent DFNB-induced contact hypersensitivity. 66…”
Section: Immune-targeted Approaches For the Suppression Of The Allementioning
confidence: 99%
“…Recent studies have demonstrated that CXCL974‐103 the COOH terminal peptide of human CXCL9 binds with high affinity to GAGs and inhibits CXCL8‐ and monosodium urate crystal (MSU)–induced neutrophil migration . In a follow‐up study, Vanheule and colleagues examined whether the chemokine‐GAG antagonist CXCL974‐103 inhibited inflammation and neutrophil‐dependent DFNB‐induced contact hypersensitivity . The authors demonstrated that simultaneous treatment of mice with CXCL974‐103 and DNFB inhibited clinical symptoms of CHS, ear swelling and that this was associated with a reduction in neutrophil infiltration and the level of the neutrophil‐derived proteolytic enzyme metalloproteinases MMP9.…”
Section: Experimental Models Of Allergic Diseasementioning
confidence: 99%